Diet-induced obesity suppresses cortical bone accrual by a neuropeptide Y-dependent mechanism. Issue 11 (November 2018) - Wee, Natalie; Enriquez, Ronaldo; Nguyen, Amy; Horsnell, Harry; Kulkarni, Rishikesh; Khor, Ee; Herzog, Herbert; Baldock, Paul
Abstract Objective To determine whether age and neuropeptide Y (NPY) were involved in the skeletal response to extended periods of diet-induced obesity. Methods Male wild-type (WT) and NPY null (NPYKO) mice were fed a mild (23% fat) high-fat diet for 10 weeks from 6 or 16 weeks of age. Metabolism and bone density were assessed during feeding. Skeletal changes were assessed by microCT and histomorphometry. Results High-fat feeding in 6-week-old WT mice led to significantly increased body weight, adiposity and serum leptin levels, accompanied with markedly suppressed cortical bone accrual. NPYKO mice were less susceptible to fat accrual but, importantly, displayed a complete lack of suppression of bone accrual or cortical bone loss. In contrast, when skeletally mature (16 week old) mice underwent 10 weeks of fat feeding, the metabolic response to HFD was similar to younger mice, however bone mass was not affected in either WT or NPYKO. Thus, growing mice are particularly susceptible to the detrimental effects of HFD on bone mass, through suppression of bone accrual involving NPY signalling. Conclusion This study provides new insights into the relationship between the opposing processes of a positive weight/bone relationship and the negative 'metabolic' effect of obesity on bone mass. This negative effect is particularly active in growing skeletons, which have heightened sensitivity to changes in obesity. In addition, NPY is identified as a fundamental driver of this negative 'metabolic' pathway to bone.